Hemoperitoneum after Ovulation in Systemic Lupus Erythematosus and Autoimmune Thrombocytopenia - Cara Buskmiller; Henri Rosenberg; Sandeep Sen (Hindawi Limited, 2019)
Background. Three prior cases of hemoperitoneum associated with immune thrombocytopenia (ITP) have been reported in adolescents. This reports a case of hemoperitoneum after ovulation in an adult. Case. A 34-year-old nulligravida presented with abdominal pain after a heavy period and rebound tenderness. Urine beta-hCG was negative, hemoglobin was 5.4, and platelet count was zero. CT revealed hemoperitoneum and contrast blush surrounding the left ovary. She was treated for newly diagnosed systemic lupus erythematosus and steroid-refractory ITP. Her platelet count and symptoms improved. Conclusion. Hemoperitoneum after ovulation in ITP is rare; this represents the first adult case in the literature and reviews differential diagnosis of thrombocytopenia. The obstetrician/gynecologist is part of a multidisciplinary team caring for patients with bleeding of gynecological origin and should withhold surgical intervention for hemoperitoneum when medical therapy is warranted.